Probable Maximum Precipitation comparison using hershfield's statistical method and hydro-meteorological method for Sungai Perak Hydroelectric Scheme - Razali J.; Sidek L.M.; Rashid M.A.; Hussein A.; Marufuzzaman M. (Science Publishing Corporation Inc, 2023)
One of the potential risks attributed to the occurrence of dam overtopping and dam wall failure due to the inadequacy of the spillway capacities is the loss of life and property damages in the downstream area. The current practices in most countries in minimizing these risks are by analyzing the extreme precipitation that leads to extreme flood. Extreme precipitation is best known as Probable Maximum Precipitation (PMP) and this estimation is useful in determining Probable Maximum Flood (PMF) in reviewing the spillway adequacy of dam structures. This paper presented PMP estimations using two approaches; physical method (Hydro-meteorological Method) and statistical approach (Hershfield's Method) at the Sungai Perak Hydroelectric Scheme that consists of four cascading dams namely Temengor dam, Bersia dam, Kenering dam and Chenderoh dam. The highest PMP estimates from these two methods will be chosen as the rainfall input to establish PMF hydrographs. Estimations using Hydro-meteorological generalized map produces 40-50% higher estimates compared to Hersfield's method with the PMP values of 550mm (1hours), 600mm (3hours), 800mm (6hours), 820mm (12hours), 1300mm (24hour) and 1600mm (72 hours). Accepting the Hydro-meteorological Method to determine PMF values for this hydroelectric scheme may be the best course since the estimations of the extreme precipitations using this method are the highest. 2018 Authors.